Effects of active versus passive recivery on power output during repeated bouts of short term, high intensity exercise - Connolly, D. A. J.; Brennan, K. M.; Lauzon, C. D. (Journal of Sports Science & Medicine, 2003)
ATP repletion following exhaustive exercise is approximated to be 90-95% complete in 3 minutes, and is crucial in the performance of short duration, high intensity work. Few studies appear to have used this 3-minute interval in the investigation of recovery modes, blood lactate accumulation and power output. Thus, our aim was to investigate changes in peak power (PP), average power (AP) and blood lactate during repeated bouts of high intensity, short duration cycling, comprising active and passive recovery modes lasting 3 minutes. Seven male cyclists (age 21.8±3.3 yrs, mass 73.0±3.8kgs, height 177.3±3.4cm) performed both an active (3 min at 80rpm & 1kg resistance) and a passive recovery (no work between bouts) protocol. Following a warm-up, subjects performed six 15-second maximal sprints against a fixed workload of 5.5kg. Mean PP across the six trials was 775±11.2Watts (W) and 772±33.4W for active and passive protocols respectively; whereas mean AP was 671±26.4W and 664±10.0W, respectively. Neither was significantly different. There was a significant difference within trials for both peak power and average power (p<0.05), with both values decreasing over time. However, the decrease was significantly smaller for both PP and AP values during the active recovery protocol (p<0.05). In the current study, variation in power output cannot be explained by lactate values, as values did not differ between the active and passive protocol (p=0.37). Lactate values did differ significantly between trials within protocols (p<0.05). The results of this study suggest that an active recovery of 3 minutes between high intensity, short duration exercise bouts significantly increases PP and AP compared to a passive recovery, irrespective of changes in blood lactate levels.